Pengaruh Voucher Terhadap Minat Kunjung Ulang Pada Pelanggan Srikandi Botanica Medan - Adrika Willis; Rehia K. Isabella Barus; Agung Suharyanto (Universitas Medan Area, 2022)
This study aims to determine the effect of giving vouchers to the revisit interest of customers at the Coffee Shop Srikandi Botanica Medan. The theories used in this research are marketing communication theory, sales promotion, revisit interest, voucher theory, and AIDDA theory. This research method is a quantitative research method. Determination of respondents in this study using a sampling technique aimed. The research subjects in this study were 100 people. Data collection techniques using questionnaires, in analyzing the data of this study using single table analysis, cross table analysis, and hypothesis testing using the correlation coefficient formula Ladder by Spearman using the Statistical Product and System Solution (SPSS) application 22. From the results of this study obtained The correlation coefficient value is 0.808 and shows a significance value smaller than 0.05, so Ho is rejected and Ha is accepted. It is known that the power of influence in this study is 65%. Shows a high relationship between the effect of vouchers on the interest of repeat customers of Srikandi Botanica Medan.